GROWTH RESPONSE OF TWO LOCAL UPLAND RICE CULTIVARS (ORYZA SATIVA L.) ON SALINITY - Maemunah Maemunah; Jeki Jeki; Mustakim Mustakim; Yusran Yusran; Ramal Yusuf; Ni luh Dian Purnama Sari (AGROLAND The Agricultural Sciences Journal (e-Journal), 2023)
Increasing the number of inhabitants in Indonesia led to the limited agricultural land so that the paddy fields become narrow and limited, the limited paddy fields caused agricultural production in Indonesia to decline while demand increased. Tidal land cultivation is still rarely performed due to the high salt content (NaCl). The purpose of this study is to obtain upland rice cultivars that are tolerant of salinity stress. The study was conducted in November to December 2019 at the Seed and Science Technology Laboratory of the Faculty of Agriculture, University of Tadulako. The study was arranged using a completely randomized design (CRD) of two factors where the first factor consisted of two levels, namely Logi, and Tako, while the second factor consisted of five levels, namely 0.5%, 0.6%, 0.7%, 0.8%, and 0.9% were repeated three times. The results showed that tako cultivars have a good tolerance to salinity stress compared to logi cultivars, tako cultivars have the fastest germination time and germination capacity above 80%. At a concentration of 0.5% can not inhibit the growth of upland rice, but at a concentration of 0.9% can inhibit the growth of upland rice.